Tax Amnesty dan Implikasinya Terhadap Reformasi Perpajakan di Indonesia - Abdul Qodir Jaelani; Udiyo Basuki (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
This paper concludes the meaning of the juridical tax amnesty is the elimination of the taxowed should not sanction tax administration and criminal sanctions in the field of taxation, by wayof uncovering treasures and pay the ransom as stipulated in the legislation of tax amnesty. Remissionof taxes (tax amnesty) done on the type of income tax, value added tax and sales tax on luxurygoods. As for his relationship with the country's financial revenue receipts can be found in Article 1,Paragraph 1 of Law No. 17 of 2003 which states that the financial state has one of the definitionsand scope of that right of the state to collect taxes. Taxes are the backbone and the main source ofstate revenue that has contributed 84.9% of total state revenue. Second, the program remission oftaxes (tax amnesty) greatly affects the improvement of tax compliance (tax payers) and provides alast chance (one shot opportunity) for taxpayers who do onshore and offshore tax evasion with theprimary purpose as a vehicle for reconciliation national taxation for all potential taxpayers andsociety is expected to push tax reforms towards a more berkeailan tax system and the expansion ofthe data base of taxation more valid, comprehensive and integrated.